Sensuality and Salvation in Keith Kachtick’s Hungry Ghost - Singh, Raj Kishor (Literary Studies, 2025)
This study paper rummages into Keith Kachtick's novel, Hungry Ghost (2003), which intricately intertwines themes of sensuality and salvation within the philosophical framework of Buddhism. It scrutinizes the transformative odyssey of Carter Cox, a 39-year-old libertine photographer unexpectedly forming a profound connection with a Buddhist mentor. Through the lens of Sallie B. King’s Buddha Nature (1991) and Geshe Kelsang Gyatso’s The Bodhisattva Vow (1991), it dissects the intricate conflict between sensuality and the pursuit of spiritual redemption. Kachtick employs a distinctive second-person narrative style, consistently addressing Carter as "you", a deliberate technique to channel Carter's Buddha nature. This manifestation of inner enlightenment grants Carter prescience, enabling glimpses into the future and insights into the minds of other characters, endowing the narrative with a quasi-third-person omniscience. This intentional narrative choice acts as a prism through which readers witness the potential repercussions of Carter's surrender to primal desires versus his embrace of his Buddha nature. The exploration reveals that, by contrasting these divergent paths, the narrative transcends traditional explorations of interpersonal conflict. It beckons contemplation on the profound implications of embracing higher consciousness among the alluring pull of sensual desires. Consequently, the novel emerges not merely as a tale of personal struggle but as a canvas showcasing the intricate interplay between individual choices, spiritual dilemmas and the transformative potential inherent within Buddhist philosophy.